Improvement of Media Competence within Cooperative Learning Process in a Vocational Education Institution - Pigozne, Tamara; Pigoznis, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Basing on the theoretical formulations concerning the functions and competence of media, as well as cooperative learning the authors developed a model aimed at improvement of media competence of the vocational education institutions’ students. The elaborated model offers teachers in various vocational educational institutions to generate and develop ideas for media competence perfection, ensuring an opportunity in an interdisciplinary project to use the multiform functions of media competence (information, technologies, computer, network, critical and visual) and cooperative learning to ensure efficient learning process. The aim of the article is to analyze the results obtained during the approbation of the model for improvement of the media competence within the cooperative learning process in a vocational education institution.